Peran Pengawas dalam Meningkatkan Mutu Guru Madrasah di MTs. Negeri 2 Aceh Tamiang - Ismail, Sulaiman; W, Sulaiman; Nur, Muhammad (LPPM Institut Nasional Laa Roiba Bogor, 2024)
One factor in the low quality of education is the need for more training for teachers in schools and madrasas. This is the task and role of supervisors in developing teachers to improve the quality of education. Therefore, the main focus of this research is to describe the role of supervisors in improving the quality of teachers in madrasas. This research is descriptive and qualitative, taking the location of MTs.Negeri 2 Aceh Tamiang is the research location. Data was collected using interviews and observations of supervisors and madrasa heads as key informants.